Broadband unidirectional generation of surface plasmon polaritons with dielectric-film-coated asymmetric single-slit - Chen, Jianjun; Li, Zhi; Ming Lei; Yue, Song; Xiao, Jinghua; Qihuang Gong (OPTICS EXPRESS, 2011)
A dielectric-film-coated asymmetric single nanoslit is proposed to realize broadband unidirectional generation of surface plasmon polaritons (SPPs). Due to the tight field confinements by the dielectric film and the deep groove in the asymmetric single slit, the transmittance of the SPPs in the groove to the left side considerably decreases. This greatly suppresses the left-propagating SPP generation efficiency for a broad bandwidth. Meanwhile, the right-propagating SPP generation efficiency has a flat spectra range because of the low transmittance, too. So the unidirectional SPP generation with bandwidth of > 100 nm around lambda = 750 nm is experimentally achieved for the device lateral dimension of only 865 nm. (C) 2011 Optical Society of America